A Dynamics Modelling of Waste management of Indonesia - Andi Muhammad Sadli (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2018)
Waste management is the collection, transport or disposal and management of waste materials. Most waste management activities are decided upon and carried out in a public, semi-public area typically involving the waste management organization, one or more regulators and other stakeholders and members of the public. The management of waste is not only the responsibility of governments, but also an individual’s duty. Waste management is an issue that has to be dealt with daily in order to control the huge amounts of waste currently passing through our towns and cities. It is main goal of this research to evaluate the performance of waste management activities. System dynamics methodology was use to study the waste management activities of a City of Indonesia in Indonesia. Waste management system quantities were identified from waste generation and waste collection activities. Thirteen quantities were identified and a causal loop diagram was developed for the system. Thereafter a stock and flow diagram was developed for the system and this depicts the dynamic relationships among system quantities. The performance of waste management technique was determine in terms of waste collected and waste in stock. A system dynamic software; Vensim PLE was used to run the system dynamic model to simulate the activities of waste management system for a period of ten years. Amount of waste collected increases as the amount waste generated increases. At waste generation factors of 80% per year and 70% per year; the amount of waste collected was 502,137 tons and 921, 794 tons respectively at the end of ten years. If the amount of resources injected into waste management is increase; the amount of collected waste will definitely increase. The model developed will help the waste managers in decision making regarding waste management.